Spin Off atau Konversi Syariah?: Studi Kebijakan Kewajiban Spin Off Unit Usaha Syariah di Indonesia - Saparuddin Siregar (Inovasi, 2023)
ABSTRACT This study aims to examine the determinants of the decision to choose a spin off or conversion from the bank's customer side. This research then relates it to making the right policy for bank shareholders to spin off or convert. The customer's decision being tested is the effect of employee competence, bank promotion, bank technology on the decision to choose Islamic banking services with customer religiosity as a mediating variable. This study uses SEM PLS analysis by taking the case of Bank SUMUT which is facing the choice to spin off or convert. The research sample of 83 customers was obtained purposively by distributing questionnaires to all branch offices of the SUMUT bank. The results showed that the competency, technology and religiosity variables had a positive and significant impact on the customer's decision to choose a spin off or conversion. However, the Religiosity Variable is not able to strengthen the influence of Competence and Technology on the Decision to choose sharia services. This study concludes that if customers feel comfortable with the competence of employees and the quality of bank technology, then the customer's decision to choose sharia services becomes rational without the need for reinforcement from religiosity. This research has implications for recommending that bank shareholders who own UUS adopt a policy of choosing to convert rather than spin off. Keywords: Competency, Conversion, Religiosity, Spin-off, Technology